2012
DOI: 10.1103/physrevb.85.165456
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical engineering of a two-band Chern insulator in two dimensions with arbitrary topological index

Abstract: Two-dimensional 2-band insulators breaking time reversal symmetry can present topological phases indexed by a topological invariant called the Chern number. We propose an efficient procedure to determine this topological index, which makes possible to conceive 2-band, tight-binding Hamiltonians with arbitrary Chern numbers. The technique is illustrated by a step by step construction of a model exhibiting five topological phases indexed by Chern numbers {0, ±1 ± 2}. On a finite cylindrical geometry, this insula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
100
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 45 publications
4
100
0
Order By: Relevance
“…When k spreads over Brillouin torus, h describes a closed surface Σ. The Chern number can then be viewed as -the (normalized) flux of a magnetic monopole located at the origin through the surface Σ -the number of times the surface Σ wraps around the origin (in particular, it is zero if the origin is « outside » Σ ; more precisely it is the homotopy class of Σ in the punctured space 3 − 0) -the number of (algebraically counted) intersections of a ray coming from the origin with Σ, which is the method used in [29].…”
Section: Berry Curvature and Chern Numbermentioning
confidence: 99%
“…When k spreads over Brillouin torus, h describes a closed surface Σ. The Chern number can then be viewed as -the (normalized) flux of a magnetic monopole located at the origin through the surface Σ -the number of times the surface Σ wraps around the origin (in particular, it is zero if the origin is « outside » Σ ; more precisely it is the homotopy class of Σ in the punctured space 3 − 0) -the number of (algebraically counted) intersections of a ray coming from the origin with Σ, which is the method used in [29].…”
Section: Berry Curvature and Chern Numbermentioning
confidence: 99%
“…Although as it is wellknown and seen of Eq.5, the time-reversal symmetry breaks when any magnetization is turned on, system remains chiralpolarized even if out-of-plane magnetization is applied 42 . In fact, by application of z-axis magnetization, as shown in Fig.2, the degeneracy of the bands with opposite chiralities breaks 44 .…”
Section: A Hamiltonianmentioning
confidence: 93%
“…where, α is the chiral index 24,41,42 which has two different signs ± corresponding to the upper and lower block digonal matrices in Eq.3. Here the last term is the mass term which its negative sign leads to topologically non-trivial band structure.…”
Section: A Hamiltonianmentioning
confidence: 99%
“…We now ask whether the driving can induce gapped phases with |c 1 | > 1. One way to address this question is to notice that in order to obtain larger Chern numbers, it is necessary to have more than one pair of Dirac points [23]. Previous studies have shown that multiphoton resonances, occurring when the Floquet bands overlap, can induce additional pairs of Dirac points, provided that TRS holds [20,24].…”
mentioning
confidence: 99%
“…Following the elegant method of the Brouwer degree developed in Ref. [23], the Chern number (of the lower quasienergy band) reads…”
mentioning
confidence: 99%